Effects of Tested Rules on Work-Rest Time in Volleyball - Stanković,Mladen (2017)
The aim of this study was to determine the influence of new rules tested at the inaugural Mens Under 23 (U23) World Championship (set to 21 points and 15 seconds between the end of a point and the new serve) on all aspects of time in volleyball matches. The study sample comprised 36 matches partially segmented into 123 sets and 4583 points played. Applying one-way ANOVA, it was shown that the active part of the set and the whole match last slightly more than one third of the total time. The most frequent rally duration was 5 to 10 seconds (43.5% of points). As sets became more unpredictable and approached the end, rest time between points was longer. Time analysis of volleyball matches is important as it helps with proper development of physical preparation for players, gives coaches insight into appropriate match flow and provides a clear time frame of each part of a volleyball match for organisers of competitive events, pools, championships and tournaments.